2022
DOI: 10.5194/bg-19-957-2022
|View full text |Cite
|
Sign up to set email alerts
|

The role of cover crops for cropland soil carbon, nitrogen leaching, and agricultural yields – a global simulation study with LPJmL (V. 5.0-tillage-cc)

Abstract: Abstract. Land management practices can reduce the environmental impact of agricultural land use and production, improve productivity, and transform cropland into carbon sinks. In our study we assessed the biophysical and biogeochemical impacts and the potential contribution of cover crop practices to sustainable land use. We applied the process-based, global dynamic vegetation model LPJmL (Lund–Potsdam–Jena managed Land) V. 5.0-tillage-cc with a modified representation of cover crops to simulate the growth of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 87 publications
2
12
0
Order By: Relevance
“…Moreover, including the no-till technique in cover cropping in our simulations had the potential to further mitigate N leaching (41% in CC L NT vs. 34% in CC L ; Table 2) mainly due to the reduced net N mineralization rates (Figure S7 in Supporting Information S1). This is in line with the findings from a meta-analysis by Thapa et al (2018) and a recent modeling study by Porwollik et al (2022).…”
Section: N Leachingsupporting
confidence: 92%
See 3 more Smart Citations
“…Moreover, including the no-till technique in cover cropping in our simulations had the potential to further mitigate N leaching (41% in CC L NT vs. 34% in CC L ; Table 2) mainly due to the reduced net N mineralization rates (Figure S7 in Supporting Information S1). This is in line with the findings from a meta-analysis by Thapa et al (2018) and a recent modeling study by Porwollik et al (2022).…”
Section: N Leachingsupporting
confidence: 92%
“…Likewise, in some arid and semi‐arid regions, as well as temperature‐limited areas in the high latitudes (e.g., Canada) a slight decrease of N leaching in response to cover cropping systems was found, as poor growth conditions constrained the CC capacity for soil N uptake. In addition, the rapid turnover rate of SOM pools driven by warm and moist climate (Olin, Lindeskog, et al., 2015), together with abundant precipitation may increase N leaching with cover crop practices in the humid tropics (Figure 6) as a result of high biomass of N returned to soils (Figure S6 in Supporting Information S1) and enhanced throughflow (Porwollik et al., 2022).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Global analysis of soil C sequestration potential should be based on a well-calibrated model on gridded NPP, proper climate and soil data, and accounting for all sources of uncertainties. For example, a recent global modelling study on the potential of cover cropping found the median global soil carbon sequestration rates of 0.48 and 0.52 t C ha − 1 yr − 1 (Porwollik et al, 2022).…”
Section: The Way Forwardmentioning
confidence: 99%